1990
DOI: 10.1007/bf01188435
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative changes of neurons in the superior cervical ganglion following an injection of Ricinus communis agglutinin-60 into the vagus nerve in hamsters

Abstract: The present study describes neuronal changes in the superior cervical ganglion of hamsters following injection of Ricinus communis agglutinin-60 (RCA-60) into the ipsilateral vagus nerve in the cervical region. There were no noticeable structural changes in the ganglion 1 day after injection. Between 3 and 15 days after injection, a small number of neurons located in the caudal part of the ganglion underwent degenerative changes including disappearance of rough endoplasmic reticulum and cytoplasmic vacuolation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…On the other hand, morphological and electrophysiological studies have provided evidence that some cranial nerves, including trigeminal (Matthews & Robinson, 1980), facial (Thomander et al. 1984; Matthews & Robinson, 1986), vagus (Ling et al. 1990) and hypoglossal (O’Reilly & Fitzgerald, 1990; Fukui et al.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, morphological and electrophysiological studies have provided evidence that some cranial nerves, including trigeminal (Matthews & Robinson, 1980), facial (Thomander et al. 1984; Matthews & Robinson, 1986), vagus (Ling et al. 1990) and hypoglossal (O’Reilly & Fitzgerald, 1990; Fukui et al.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that the postganglionic sympathetic fi bers which originate from the superior cervical ganglion (SCG) travel along the nerve plexuses of the internal and external carotid arteries [Bowers and Zigmond, 1979;Marfurt et al, 1986;Tamamaki and Nojyo, 1987;Buller and Bolter, 1997]. Both the morphological and electrophysiological studies have provided evidence to suggest the existence of sympathetic fi bers traveling along some cranial nerves including the vagus and the hypoglossal nerves Robinson, 1980, 1986;Thomander et al, 1984;Ling et al, 1990;O'Reilly and Fitzgerald, 1990;Takeuchi et al, 1993]. In this connection, Fukui et al [1992] had demonstrated the labeling of SCG following the application of horseradish peroxidase (HRP) to the hypoglossal nerve trunk in cats.…”
Section: Introductionmentioning
confidence: 99%
“…When examined 4 to 7 days after the blast exposure, ultrastructural analysis using electron microscopy revealed neurons with darkened dendrites (dark appearance of cytoplasm within dendritic processes). Darkened dendrites can indicate that neurons are in an atrophic state due to trauma and have been reported following axotomy and exposure to neurotoxins (37,38). Additionally, microglia at this same time point exhibited morphological changes and proliferation, suggesting a massive inflammatory response mediated by microglia.…”
Section: Anatomical Evidence For Noise-induced Damage To Central Vestmentioning
confidence: 55%